The Effect of a Multifactor Orientation on Student Performance: Organizational Skills, Goal setting, Orientation to Classroom, and Academic Support - McKenna, Barbara M.; Finamore, Dora; Hewitt, Valerie; Watson, Linda; Millam, Loretta A.; Reinhardt, Michelle (Online Learning, 2019)
Online classes have significantly increased over the last 20 years. From a simple asynchronous model to a complex, interactive, live system, they challenge many online students. Based on Knowles’ Andragogy theoretical framework, researchers sought to explore the qualities students need to complete a first term undergraduate online course. Researchers conducted a quantitative exploratory study to identify the effects of offering a multifactor orientation; this was an extra seminar online, focused on organizational skills, goal setting, orientation to the online classroom, and academic support for successfully completing a first term class. Participants at an online university in a first term course agreed to attend a faculty- led, one-hour presentation; this was an extra seminar focusing on organizational skills, goal setting, orientation to the online classroom, and academic support. A total of 25 students volunteered and attended the extra seminar, provided by three faculty members who were experienced in teaching first-term students in a school of business at a large online university. There was a total of six separate classes of students, each attending a first-term, 10-week course, Academic Strategies for the Business Professional. The course is a combination of synchronous live seminars- and other asynchronous interactive exercises, focusing on providing a foundation for secondary learning. Students in three of those classes were invited to participate. Three faculty members randomly selected a section of this course prior to the beginning of a new term. Once the term started, the faculty, during the first regular live seminar, invited their respective students to the selected treatment class. A total of 144 students were still on the roster at the end of the courses. Of those, 25 were male (17%). There were only 35 males in all the classes, 24% of the total number of students, so the percentage of males in the treatment group was less than the number of males in all the courses. The average number of males (25%) are enrolled in the school. There was no compensation for attending the extra seminar and an IRB approved the study. The students in the treatment groups were told that they could drop out of the study at any time without penalty and this was detailed in the signed consent form, using Survey Monkey. The final grades for students were compared by an instructor who did not teach one of the treatment classes via a single-factor ANOVA to determine if there was any significant difference in the way each instructor graded. With a p-value of .74, no significant difference was found among the three instructors (Table 1). The final grades of students who did not attend the seminar were compared to the final grades of the students who attended the extra seminar via a single-factor ANOVA to determine if there was a difference in the final grades for those who attended the extra seminar versus those who did not. With a p-value of .03, the grades of those who attended the extra seminar were significantly higher than those who did not (Table 2). Though the n was small, this study indicates that students who received additional help, if only a single extra seminar, may have benefited by earning higher final grades than those students who did not receive the additional instructions. The average grade for the students who did not attend the extra seminar was 58.8%; compared to 79.5% for students who attended the seminar. The students in all classes had continued support services through regular emails, announcements, and resources from faculty, after the multifactor orientation. In other words, the only difference in the classes was that some students had the opportunity to attend an extra seminar and some did not.